CRIMINAL LIABILITY FOR FRAUD IN CAMPAIGN FINANCE REPORTS FOR LEGISLATIVE ELECTIONS IN INDONESIA - Antari, Putu Eva Ditayani; Darmanata, Made Swarna (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Article 280 of Law Number 8 of 2012 concerning Reporting Campaign Fund Fraud obscures the norm that only legislative candidates are responsible and not political parties. This represents a country that operates a democratic system, and freedom of speech and writing is guaranteed by the state and the constitution. Freedom of expression is regulated in Article 1 (1) of Law Number 9 of 1998 concerning Freedom of Expression in Public. Campaign funds are the most important key to honest elections and reflect the ugliness of fraudsters who, if fraud occurs in campaign funds, lead to corrupt electoral practices, namely political corruption of the organizers. In 2019, there were allegations of fraud in the reporting of campaign funds for candidate BuIeeng Dapi from the BaII National Democratic Party in the 2019 general election. It was Somvir who reported the campaign funds. The results of this research show that responsibility for fraud is based on the principle of vicarious responsibility and administrative sanctions. And the types of sanctions given are criminal sanctions and fines in accordance with Article 334 paragraph (1), paragraph (2), and/or paragraph (3) and Article 335 paragraph (1), paragraph (2), and/or paragraph (3 ) Law Number 7 of 2017. Keywords: Inconsistency, Position, CorruptionKeywords: Fraud, CriminaI, General EIection